1998
DOI: 10.1063/1.368579
|View full text |Cite
|
Sign up to set email alerts
|

Back-channel-oxidized a-Si:H thin-film transistors

Abstract: We have developed a back-channel-oxidized thin-film transistor (TFT) structure which does not require the conventional etching of the n+-a-Si:H layer from the channel region. Key processes in the fabrication of this structure are the deposition of a very thin (less than 10 nm) n+-a-Si:H layer with low resistivity (∼50 Ω cm), and an oxygen plasma treatment to change the n+-a-Si:H layer above the channel region into dielectric oxide. With a thin (∼50 nm) a-Si:H layer, the back-channel-oxidized TFT structure make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…11) The thickness of the a-Si:H layer is 30 nm. The structure of the a-Si:H TFT is a back-channel-etched type without an ordinary SiN x passivation layer.…”
Section: Methodsmentioning
confidence: 99%
“…11) The thickness of the a-Si:H layer is 30 nm. The structure of the a-Si:H TFT is a back-channel-etched type without an ordinary SiN x passivation layer.…”
Section: Methodsmentioning
confidence: 99%
“…Before the photosensitive organic passivation is spun on, the back channel of TFT is dealt with the oxygen plasma treatment, and a thin oxide layer of about 3nm to 5nm is formed in the back channel interface. The thin oxide layer can be used for the anti-water absorption layer of the active region [2,3]. The ITO film is then deposited and patterned as the pixel electrodes on the passivation layer.…”
Section: Methodsmentioning
confidence: 99%
“…This would also help to improve the switching behavior of the transistor. It is noteworthy here that Takechi et al 22 observed the similar drastic improvement in TFT performance by modulating the channel chemistry through the oxygen plasma-induced oxidation of n ϩ amorphous silicon above the channel region into dielectric oxide. The higher performance of such back channel oxidized a-Si:H TFTs was reported to be due to lower density of back-channel defect states.…”
mentioning
confidence: 91%